Rapid synthesis of zinc oxide nanoforest: use of microwave and forced seeding. (5th December 2016) - Ghosh, S; Chakraborty, J
Abstract: A rapid synthesis technique has been developed for zinc oxide (ZnO) nanoforest using microwave assisted hydrothermal method. This microwave assisted process takes less than 4 h whereas conventional hydrothermal synthesis takes 25 h to fabricate nanoforest of comparable dimensions. The simple dipping technique for secondary seeding on the primary nanorods has been studied and it has been shown that such seeding would take at least an hour. A 'forced seeding' technique has been developed which reduces the seeding time drastically. The microwave assisted branch growth occurs at a speed of 10 nm min −1 which is 10 fold faster than that of hydrothermal method.